Assessing Nurse Educators' Competencies for Adopting Blended Learning in the Skills labs in Uganda's Public Nursing Schools - Nampiima, Eva Kakonge; Mulumba, Mathias Bwanika; Musisi, Badru; Nakate, Grace (RA Journal of Applied Research, 2024)
Blended learning has become an integral part of nursing education, offering a blend of online and face-to-face instruction that enhances learning experiences, particularly within skills labs. However, the effectiveness of blended learning largely depends on the competencies of nurse educators in utilizing digital tools and methodologies. This study assessed the competencies of nurse educators in Uganda's public nursing schools concerning blended learning adoption. Data was collected from 40 randomly selected nursing educators in 4 public nursing schools in Uganda. The findings indicate significant inadequacies: only 25% are proficient with Learning Management Systems (LMS) like Moodle, 20% can effectively use platforms like Zoom and Microsoft Teams for synchronous sessions, 30% are adept at using social media platforms such as WhatsApp and YouTube for informal learning and networking, and merely 12.5%are proficient in using television videos as supplementary educational resources. These results highlight a critical need for targeted professional development and training programs to enhance the digital competencies of nurse educators. Addressing these gaps is essential for the effective implementation of blended learning, ultimately aiming to improve the quality of nursing education in Uganda and foster the development of skilled nursing professionals